Food Management Study At Muhammadiyah Hospital Ahmad Dahlan Kediri City - Salma Balqis; Amarin Yudhana; Wahyu Purnomo Jati; Laili Wulandari (Journal of Hospital Management and Services, 2024)
Food service can be interpreted as an integrated system activity, related to one another. The purpose of this study was to find out an overview the management of food service in Muhammadiyah Ahmad Dahlan Hospital, Kediri City.The research design used is a qualitative method. The location of the research was carried out at Muhammadiyah Ahmad Dahlan Hospital, Kediri City. Sources of data using the interview method. The sampling technique used was purposive sampling. The univariate variable of this research is the study of food management in Muhammadiyah Ahmad Ahmad Hospital, Kediri City. This research was conducted on August 12, 2021. Data processing includes data reduction, data presentation, and data verification. The results of this study were analyzed using a qualitative approach with triangulation techniques.The results showed that most of the management of food service in Muhammadiyah Ahmad Dahlan Hospital, Kediri City, was in accordance with the standards. It should be noted that the distribution process is related to patients who are positive for the corona virus. In this case for food distribution, pay more attention to the portion, color, and taste of food.